Analysis Of Product Design And Product Quality To Purchase Decisions - Desthilia Hendra Ananda; Rita Tri Yusnita; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This study aims to determine the analysis of product design and product quality on purchasing decisions (a survey of consumers who buy bag products at the Tazik Art Shop). The method used is a quantitative approach with the survey method. With a research sample of 100 consumers who buy bag products at the Tazik Art Shop. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the design of the bag product at the Tazik Art Shop shop had a very good rating classification, the quality of the bag product at the Tazik Art Shop shop had a very good rating classification, the decision to buy a bag at the Tazik Art Shop shop had a good rating classification. Simultaneously product design and product quality have a significant influence on purchasing decisions. Partially Product Design has an insignificant effect on the increase in purchasing decisions, partially Product Quality has a significant effect on purchasing decisions